2004
DOI: 10.1530/eje.0.1500371
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization of mouse ZAKI-4 gene that encodes ZAKI-4 alpha and beta isoforms, endogenous calcineurin inhibitors, and changes in the expression of these isoforms by thyroid hormone in adult mouse brain and heart

Abstract: OBJECTIVE: ZAKI-4 was identified as a thyroid hormone-responsive gene in cultured human fibroblasts. A single ZAKI-4 gene encodes two isoforms, ZAKI-4 alpha and beta, both inhibiting calcineurin activity. ZAKI-4 alpha and beta differ at their N termini, and show distinct distribution profiles in human tissues. The aim of this study was to elucidate the organization of the mouse ZAKI-4 gene and to determine the effect of thyroid hormone on the expression of ZAKI-4 isoforms in vivo. DESIGN: We cloned mouse homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…In mice, two splice variants of Rcan2 that display distinct tissue-specific expression patterns have been identified (Mizuno et al, 2004): Rcan2-3 is expressed predominately in the brain, whereas Rcan2-1 is also expressed in other tissues, such as the heart and skeletal muscle. Recently, it was reported that loss of Rcan2 function in mice did not affect their linear growth (Bassett et al, 2012), but significantly ameliorated age-and dietinduced obesity by causing a reduction in food intake (Sun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, two splice variants of Rcan2 that display distinct tissue-specific expression patterns have been identified (Mizuno et al, 2004): Rcan2-3 is expressed predominately in the brain, whereas Rcan2-1 is also expressed in other tissues, such as the heart and skeletal muscle. Recently, it was reported that loss of Rcan2 function in mice did not affect their linear growth (Bassett et al, 2012), but significantly ameliorated age-and dietinduced obesity by causing a reduction in food intake (Sun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the neonatal rat brain, expression of ZAKI-4 mRNA in cerebral cortex gradually increases with age but the increase is attenuated in hypothyroid pups [26]. Recently, we have also shown in the adult mouse brain that the expression of ZAKI-4 a mRNA is significantly decreased by hypothyroidism [19].…”
Section: Introductionmentioning
confidence: 79%
“…We have previously shown by Northern blot analysis that both ZAKI-4 a and b mRNAs are abundantly expressed in the brain [4,19]. The abundant expression of ZAKI-4 isoforms in brain is distinct among endogenous calcineurin inhibitors that contain an ISPPxSPP motif.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations